NAMES OF THE ETHNOGRAPHIC GROUPS IN THE DICTIONARY OF CONTEMPORARY LATVIAN LANGUAGE - Kļavinska, Antra (Via Latgalica, 2017)
Determination of the ethnonymic lexical semantics can be considered as one of the aspects of ethnic studies in linguistics. Who are the Latgalians, Latgals, Suits, Selonians and other ethnographic groups, according to the modern concepts? The answer to this question can be found in the Dictionary of Contemporary Latvian Language (MLVV), which is fully available on the Internet since 2014.The aim of the paper is to analyse the names of Latvian ethnographic groups and the principles of defining meanings in MLVV, especially focusing on issues related to names of Latgalian Latvians. Lexicographic data analysis and contextual approach are applied in this research with the help of which extralinguistic factors (linguistic and situative context) are revealed.One of the most important tasks in lexicographic work is the inventory of the material, in other words, selection of word entries, illustrative texts, collection and classification of information from preceding dictionaries. In the present paper, the electronic version of the eight-volume Dictionary of the Literary Latvian Language (1972–1996) has been used for comparison. The Balanced Corpus of Modern Latvian, consisting of 4.5 million word use cases, is applied to determine the contextual semantics and the usage frequency of the names of ethnographic groups.MLVV materials show that there is a lack of consequence in the designation of ethnographic groups and definition of their meaning. The names of ethnographic groups (as well as other ethnonyms) as entries are mostly provided in the plural, for instance, latgalieši, suiti, zemgalieši (Latgalians, Suits, inhabitants of Zemgale), etc., some of them in singular forms: kurzemnieks, vidzemnieks (inhabitant of Kurzeme, inhabitant of Vidzeme). In the previously published Dictionary of the Literary Latvian Language, the names are provided in the plural, and the data of the modern Latvian language corpus show that all the analysed lexemes are used in plural form more often.The definitions of the meanings are lacking consistency. Firstly, the scope of definitions is broad: the territorial belonging to a certain Latvian ethnographic region is taken as a basis for all the explanations of the meaning; some definitions have references to linguistic and cultural peculiarity. Secondly, none of definitions has a reference that it is an ethnographic group of Latvians; only in one case, the designation of ethnic origin latvieši (Latvians) is provided. The explanation ‘inhabitants’ (of the region) is applied most often, which indicates the belonging of the lexeme to katoikonyms, not ethnonyms; also, the explanation ‘indigenous inhabitants’ (of the region) indicates indirectly that they might be Latvians.The novelty of the dictionary is that there are two meanings for the lexemes latgaļi (Latgalians) and sēļi (Selonians): the first one characterizes the Baltic tribes, the second – inhabitants/ natives of the cultural historical region (more precisely – ethnographic group of the Latvian nation). At the same time, it is not considered that lexemes latgalieši, kurzemnieki, vidzemnieki, zemgalieši (Latgalians, inhabitants of Kurzeme, Vidzeme, Zemgale) in contemporary Latvian also have at least two meanings: the meaning of ‘ethnographic group of the nation’ in modern texts, especially in the media, is complemented by a more general meaning of ‘inhabitant of the region’, in other words, the ethnonym becomes a katoikonym.The advantage of the electronic dictionary of contemporary Latvian is the possibility to edit it constantly; therefore, it is worth to pay attention to separate lexical semantic groups when developing the dictionary. In that way, it will be possible to avoid inconsistency in definitions of meanings. In order to separate ethnonyms from katoikonyms, in the definitions of the ethnonyms analysed in the paper, the designation of ethnic community ‘ethnographic group of Latvian nation’ can be applied as the main component, supplemented by semes indicating the connection with a certain territory, and possibly, the characterization of cultural, religious and linguistic peculiarity.